1995
DOI: 10.1073/pnas.92.13.6007
|View full text |Cite
|
Sign up to set email alerts
|

The inositol 1,4,5-trisphosphate receptor is essential for T-cell receptor signaling.

Abstract: Antigen-specific activation ofT lymphocytes, via stimulation of the T-cell antigen receptor (TCR)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
111
2
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(119 citation statements)
references
References 36 publications
(25 reference statements)
5
111
2
1
Order By: Relevance
“…Several models for Ca 2ϩ channels in the plasma membrane of T lymphocytes have been proposed, including IP 3 receptor (IP 3 R) Ca 2ϩ channels, mammalian homologues of transient receptor potential (TRP) Ca 2ϩ channels, and L-type voltage-dependent Ca 2ϩ channels (VDCCs). Initially, investigators suggested that a plasma membrane IP 3 R Ca 2ϩ channel, similar to the IP 3 R found in the ER, was responsible for Ca 2ϩ influx in T lymphocytes (9). A recent study confirmed that T lymphocytes express three isoforms of the IP 3 R Ca 2ϩ channel as integral plasma membrane proteins (10).…”
mentioning
confidence: 72%
“…Several models for Ca 2ϩ channels in the plasma membrane of T lymphocytes have been proposed, including IP 3 receptor (IP 3 R) Ca 2ϩ channels, mammalian homologues of transient receptor potential (TRP) Ca 2ϩ channels, and L-type voltage-dependent Ca 2ϩ channels (VDCCs). Initially, investigators suggested that a plasma membrane IP 3 R Ca 2ϩ channel, similar to the IP 3 R found in the ER, was responsible for Ca 2ϩ influx in T lymphocytes (9). A recent study confirmed that T lymphocytes express three isoforms of the IP 3 R Ca 2ϩ channel as integral plasma membrane proteins (10).…”
mentioning
confidence: 72%
“…Such a systematic apposition has not been described in electronic microscopy studies. Furthermore, in IP 3 Rdeficient cells, ionomycin or thapsigargin are perfectly efficient in eliciting a capacitative Ca 2+ entry (Broad et al, 2001;Jayaraman et al, 1995).…”
Section: Ca 2+ Influxmentioning
confidence: 99%
“…IP 3 Rs dominantly control the initiation of IP 3 -induced calcium release, demonstrated by using antisense knockdown of IP 3 R to block calcium release from the ER (20). Jurkat T cells express three IP 3 R isoforms, IP 3 R-1, IP 3 R-2, and IP 3 R-3 (21), which differ significantly in their sensitivity to IP 3 (22,23).…”
mentioning
confidence: 99%